Abnormal Return Analysis Before and After General Election in Asia - Steven Lesmana; Sumani (The Winners, 2022)
The research aimed to examine the capital market`s reaction to political events as seen from the abnormal return using the event study concept. Since there are conflicting results of similar previous studies, further research is needed. The research used event study methods, cumulative average abnormal return (CAAR) to compare abnormal returns during the general election. The research intended to compare stock market activities where there are general elections in four countries in Asia which conduct general elections every five years, and with the condition that the general elections in those countries must be completed within one day. The calculation was carried out on the stock index`s daily data representing the country in the last five events general elections in each country. The research used an estimated period of 120 days and a time of observation of 33 days. Research shows no significant difference between the average abnormal returns before and after the general election event in the last five events for all the countries tested. It can occur due to various factors, such as the anticipation made by investors, investors' behavior, and the amount and speed of information circulating. Further research is required to find out the form of the country`s efficient market.